ChemInform Abstract: Transition‐Metal‐Free Direct Arylation: Synthesis of Halogenated 2‐Amino‐2′‐hydroxy‐1, 1′‐biaryls and Mechanism by DFT Calculations. Issue 44 (14th October 2013) - Gao, Hongyin; Ess, Daniel H.; Yousufuddin, Muhammed; Kuerti, Laszlo
Abstract The reaction proceeds with complete regioselectivity to afford the target compounds, which are difficult to prepare using other methods.